The Influence of Tepuk TebakGames as Occupational Health and Safety Education on the Knowledge Level of Hair Salon Workers and Custome - Rizallihadi, Muhammad Ditra; Amalia, Elma Nurul; Oktriyani, Sharon; Dimas, Sifa Sabani; Fadil, Harisha (Universitas Negeri Semarang, 2024)
Working in a hair salon involvesexposure to various potential hazards, such as harmful chemicals from hair care products, the risk of injury from sharp tools, and non-ergonomic working postures. These issues can be addressed by enhancing workers' knowledge of occupational safety and health practices by providingeducation using available educational media. This study aims to analyze the impact of implementing educational media in the form of games on increasing knowledge among salon workers and clients using salon services. The research method used is a pre-experimental study with a single-group pre-test and post-test design. The data obtained comes from two types of sources: primary data and secondary data. Primary data were collected through interviews and direct field observations using a questionnaire as the research instrument, while secondary data were obtained through a literature review. The study showed a significant increase in workers' knowledge after being educated through games. The average knowledge score of workers increased from 45 (pre-test) to 97.5 (post-test). Similarly, salon clients' knowledge also significantly increased from an average score of 67.76 (pre-test) to 93.16 (post-test), with a p-value (<0.001)